2009
DOI: 10.1002/dvdy.22072
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing canonical Wnt signaling during mouse craniofacial development

Abstract: Wnt signaling is critical for proper development of the head and face in the mouse embryo, playing important roles in various aspects of craniofacial development ranging from axis formation to survival of cranial neural crest cells to patterning of the brain. The signaling requirements for the development of different cell lineages in the head and face are active areas of investigation. In this study, we use a recently developed TCF/Lef-LacZ transgenic reporter mouse to characterize the expression of canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 22 publications
3
51
0
2
Order By: Relevance
“…4A,D,G), nuclear -catenin localization (see Fig. S2-C in the supplementary material) and Wnt signaling reporter activity (Mani et al, 2009). Simultaneously, the onset of the earliest dermal progenitor marker expression, Dermo1 (Atit et al, 2006;Li et al, 1995;Ohtola et al, 2008), was also observed in the En1 lineage-marked cells and Axin2-expressing supraorbital mesenchymal cells (Fig.…”
Section: T1mentioning
confidence: 81%
“…4A,D,G), nuclear -catenin localization (see Fig. S2-C in the supplementary material) and Wnt signaling reporter activity (Mani et al, 2009). Simultaneously, the onset of the earliest dermal progenitor marker expression, Dermo1 (Atit et al, 2006;Li et al, 1995;Ohtola et al, 2008), was also observed in the En1 lineage-marked cells and Axin2-expressing supraorbital mesenchymal cells (Fig.…”
Section: T1mentioning
confidence: 81%
“…5 R-U). Normal development of peripheral eye structures is also regulated by Wnt signaling (10)(11)(12)31), with Wnt2b and Fzd4 acting as the primary Wnt ligand and receptor in this context. In situ hybridization analysis of the expression pattern of Wnt2b and Fzd4 at E15.5 eye showed increased and expanded expression of both these genes in the peripheral eye of TSK −/− mice compared with WT mice (Fig.…”
Section: Wnt-3amentioning
confidence: 99%
“…5) (Liu et al, 2005; Bonilla-Claudio et al, 2012), while canonical Wnt signaling is detected throughout the proximal-distal axis of the mandibular arch (Fig. 6) (Mani et al, 2010). Hence, based solely on their expression, it is unclear whether these pathways interact in mandibular arch development.…”
mentioning
confidence: 99%